1969
DOI: 10.1111/j.1478-4408.1969.tb02854.x
|View full text |Cite
|
Sign up to set email alerts
|

Graft Polymerisation of Methacrylic Acid on Nylon 6 Film

Abstract: The grafting of methacrylic acid on to nylon 6 film has been investigated; in this work, graft polymerisation was initiated by irradiation in the presence of benzophenone as photosensitiser. Little homopolymer is produced under any of the conditions investigated. Because of the rapid decomposition of the photosensitiser, graft polymerisation is efficient only at low concentrations of monomer; at high concentrations, the reaction takes onthe form of a ‘dead‐end’ polymerisation. The initial modulus of the nylon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The surface is then dried to remove the solution, leaving behind BP . The all-dry method exposes the to-be-grafted surface to BP vapor, and the surface uptakes BP during the exposure. Although different, these three categories use the same type II behavior of BP under UV irradiation, resulting in abstraction of labile hydrogen atoms from the surface to create chain-initiating radicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface is then dried to remove the solution, leaving behind BP . The all-dry method exposes the to-be-grafted surface to BP vapor, and the surface uptakes BP during the exposure. Although different, these three categories use the same type II behavior of BP under UV irradiation, resulting in abstraction of labile hydrogen atoms from the surface to create chain-initiating radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The envisioned scheme combines the benefits of iCVD and grafting by exposing surfaces to vapors of a type II photoinitiator, BP. All-dry vapor-phase photografting has been demonstrated, but lacks characterization for key features such as molecular weight and graft density. The goal of this work is to use an existing CVD chamber to perform and extensively characterize films produced by solventless grafting, hereby referred to as grafting CVD (gCVD), onto both flat and textile polymer substrates.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests an Hemoglobin washability of grafted nylon-6 improvement in the hydrophilic properties, which are related to the washability. On the other hand, it has been reported that KOH (Hegazy et al, 1990) or Na 2 CO 3 (Howard et al, 1969) as well as NaOH can be used in the solution of neutralization treatment after graft polymerization, and the hydrophilic property of the grafted substrate is improved remarkably by post-treatment in any case.…”
Section: Hydrophilic Propertymentioning
confidence: 99%
“…Here, polymer samples were irradiated in a solution containing a vinyl monomer and a photosensitizer5 or were irradiated after the surface of the sample was saturated with such a solution. 6 There are a few reports describing high-energy radiation-induced, ionic graft polymerization.7,8 Evidence for an ionic mechanism is generally the successful grafting of a monomeric species, such as a vinyl ether, that is not prone to radical-initiated polymerization.…”
mentioning
confidence: 99%